Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Answer:
[tex]m = \frac{1}{12}[/tex]
Step-by-step explanation:
Given
[tex](x,y) = (36,6)[/tex]
[tex]f(x) = \sqrt x[/tex] ----- the equation of the curve
Required
The slope of f(x)
The slope (m) is calculated using:
[tex]m = \lim_{h \to 0} \frac{f(a + h) - f(a)}{h}[/tex]
[tex](x,y) = (36,6)[/tex] implies that:
[tex]a = 36; f(a) = 6[/tex]
So, we have:
[tex]m = \lim_{h \to 0} \frac{f(a + h) - f(a)}{h}[/tex]
[tex]m = \lim_{h \to 0} \frac{f(36 + h) - 6}{h}[/tex]
If [tex]f(x) = \sqrt x[/tex]; then:
[tex]f(36 + h) = \sqrt{36 + h}[/tex]
So, we have:
[tex]m = \lim_{h \to 0} \frac{\sqrt{36 + h} - 6}{h}[/tex]
Multiply by: [tex]\sqrt{36 + h} + 6[/tex]
[tex]m = \lim_{h \to 0} \frac{(\sqrt{36 + h} - 6)(\sqrt{36 + h} + 6)}{h(\sqrt{36 + h} + 6)}[/tex]
Expand the numerator
[tex]m = \lim_{h \to 0} \frac{36 + h - 36}{h(\sqrt{36 + h} + 6)}[/tex]
Collect like terms
[tex]m = \lim_{h \to 0} \frac{36 - 36+ h }{h(\sqrt{36 + h} + 6)}[/tex]
[tex]m = \lim_{h \to 0} \frac{h }{h(\sqrt{36 + h} + 6)}[/tex]
Cancel out h
[tex]m = \lim_{h \to 0} \frac{1}{\sqrt{36 + h} + 6}[/tex]
[tex]h \to 0[/tex] implies that we substitute 0 for h;
So, we have:
[tex]m = \frac{1}{\sqrt{36 + 0} + 6}[/tex]
[tex]m = \frac{1}{\sqrt{36} + 6}[/tex]
[tex]m = \frac{1}{6 + 6}[/tex]
[tex]m = \frac{1}{12}[/tex]
Hence, the slope is 1/12
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We hope this was helpful. Please come back whenever you need more information or answers to your queries. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.